'The Treasure Within' and 'Learning Through Life': A Review and Prospectus. (19th April 2015) - Schuller, Tom; Watson, David
<x xml:space="preserve">Abstract</x> In this article, Tom Schuller and David Watson, who were responsible for a major review of lifelong learning in the UK published in 2009, describe the main proposals from that review and compare them with the 1996 UNESCO report, The Treasure Within. They find many points of similarity, as well as clear differences. Apart from specific differences of analysis or emphasis, their 2009 'Learning Through Life' (LTL) report focused particularly on adults and dealt prominently with workplace and community‐based opportunities compared with the full life‐cycle but largely formal education focus of the Delors report. They discuss the LTL 4‐lifestage model, the lifecycle distribution of resources, and entitlements to learning. They draw out key issues related to 'learning to be'. They provide a stocktake of the progress that has been made in the UK since the publication of their report in 2009 and find little grounds for encouragement that their suggested directions for change have been put into practice. They reflect on rationales and developments to offer a prospectus for lifelong learning that has general application, not only in the UK.